?GENETIC STUDIES OF COTTON (GOSSYPIUM HIRSUTUM L) I. COMBINING ABILITY AND HETEROSIS STUDIES IN YIELD AND YIELD COMPONENTS (Biological Sciences - PJSIR, 1998)
To estimate the heterosis and combining ability effects in cotton, 4 x 4 diallel cross experiment was con- ducted. Significant general combining ability effects were observed in seed cotton yield, bolls per plant, plant height, seeds per boll and seed index, (100 seed weight), whereas specific combining ability effects were significant for seed cotton yield, bolls per plant, boll weight, seed index and non significant for plant height and seeds per boll. Reciprocal effects were observed for seed index only. B557 was the best general com- biner for seed cotton yield, bolls per plant and plant height. Heterosis and heterobeltiosis were observed for all the characters under study.